Dual liquidity crises under alternative monetary frameworks: a financial accounts perspective - Ulrich Bindseil; Adalbert Winkler (European Central Bank (ECB), 2012)
This paper contributes to the literature on liquidity crises and central banks acting as lenders of last resort by capturing the mechanics of dual liquidity crises, i.e. funding crises which encompass both the private and the public sector, within a closed system of financial accounts. We analyze how the elasticity of liquidity provision by a central bank depends on the international monetary regime in which the relevant country operates and on specific central bank policies like collateral policies, monetary financing prohibitions and quantitative borrowing limits imposed on banks. Thus, it provides a firm basis for a comparative analysis of the ability of central banks to absorb shocks. Our main results are as follows: (1) A central bank that operates under a paper standard with a flexible exchange rate and without a monetary financing prohibition and other limits of borrowings placed on the banking sector is most flexible in containing a dual liquidity crisis. (2) Within any international monetary system characterized by some sort of a fixed exchange rate, including the gold standard, the availability of inter-central bank credit determines the elasticity of a crisis country's central bank in providing liquidity to banks and financial markets. (3) A central bank of a euro area type monetary union has a similar capacity in managing dual liquidity crises as a country central bank operating under a paper standard with a flexible exchange rate as long as the integrity of the monetary union is beyond any doubt.
Keywords: E50; E58; 330; bank run; central bank co-operation; Gold Standard; liquidity crisis; sovereign debt crisis